Caracterização da diversidade e do ambiente de área em recuperação florestal após dez anos de implantação - Bertolini, Íris Cristina (2019)
The objective was to characterize the diversity of substrates: arboreal, regenerator and seed bank, in order to reflect on the changes in forest species, and to analyze the physical properties of the soil, comparing an area with the recovery in the tropical forest. The study was developed at the State University of the Center-West, in Guarapuava - PR, with the objective of recovering one hectare. It was planted in 2007, planting seedlings intercalating between pioneers and nonpioneers (3 x 2 m). DBH > 5 cm, a stratification was performed according to the basal area: lower basal area - T1, basal intermediate area - T2 and upper basal area - T3. To evaluate the regeneration and the seed bank, 50% of the plots of each treatment were selected. For regeneration three subplots were installed, measured with a height of 0.2 to > 1.3 m and Dap <5 cm. The plants were sampled and solubilized at 0.25 x 0.25 x 0.05 m at the end of each season, taken to germinate in domestic vegetation and as seedlings were quantified. The phytosociological and floristic diversity parameters were calculated for the three strata. To evaluate the increment, 43 trees of S. terebinthifolius, 38 M. scabrella and 30 B. forficata were translated. Physical soil samples were collected at depths of 0 - 0.1 m, 0.1 - 0.2 m and 0.2 - 0.3 m, in the two forest areas. In the arboreal stratum were sampled 729 ind.ha-1, in 20 species and 15 families. At regeneration, 832 ind.ha-1 were sampled in 15 families and 22 species. In the bank of were were sampled 11,074 ind.m², in 80 species and 42 families. The mean diameter increase for M. scabrella was 1.51 cm.year-1, for S. terebinthifolius was 1.09 cm.year-1 and 0.73 cm.year-1 for B. forficata. Combinations and effects increased in species growth. The area in recovery process is larger in relation to soil and penetration capacity, lower macroporosity and porosity in relation to a forest in secondary succession, in the three studied depths. Planting of seedlings facilitated natural regeneration (13 species) and the seed bank presented a large number of species (80), the first being the maintenance of the forest, which are present in the first phase of regeneration.